Adv. J. Grad. Res. 2017
DOI: 10.21467/ajgr.1.1.40-48
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Mechanical Properties of Sisal Fiber Reinforced Polymer Composites

Abstract: The aim of this work is to study the influence of sisal fiber content on mechanical (i.e. tensile, flexural, impact, hardness and abrasion resistance) and thermal (i.e. TGA) properties of composites by varying the fiber and epoxy percentage. The composite was prepared by melt-mixing method, followed by compression molding process. The percentage of sisal fiber is varied from 4% to 10% in steps of 2%. Similarly epoxy content is varied from 96% to 90% in steps of 2%. Detailed mechanical Properties of Sisal Fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The model terms are significant when p-value, which is less than 0.0500 in the ANOVA table. 37 The ANOVA for the second-order model for equation (2) has been presented in Table 5, for equation (3) it is presented in Table 6, for equation (4) it is presented in Table 7 and for equation (5) is shown in Table 8, respectively. It is observed that the model p-values from Tables 5 to 8 are significant.…”
Section: Empirical Model and Data Analysismentioning
confidence: 99%
“…The model terms are significant when p-value, which is less than 0.0500 in the ANOVA table. 37 The ANOVA for the second-order model for equation (2) has been presented in Table 5, for equation (3) it is presented in Table 6, for equation (4) it is presented in Table 7 and for equation (5) is shown in Table 8, respectively. It is observed that the model p-values from Tables 5 to 8 are significant.…”
Section: Empirical Model and Data Analysismentioning
confidence: 99%
“…The use of natural plant fibers as a reinforcement in fiberreinforced plastics (FRP) to replace synthetic fibers such as glass is receiving attention, because of advantages such as renewability, low density, and high specific strength. Recent studies have investigated the development of biodegradable composite materials using natural fibers such as flax [6], silk [7] bamboo [8], pineapple [9][10], oil palm empty fruit bunch [11][12], rice husk [13], jute [14], kenaf [15], sisal [16][17], and ramie [18] as reinforcement for biodegradable plastics. A property of plant fibres depends primarily on the nature of the plant, locality in which it is grown, age of the plant, and the extraction method used.…”
Section: Introductionmentioning
confidence: 99%